PELAKSANAAN GERAKAN LITERASI DI SDN 88 PEKANBARU - dafit, Febrina; Hamidah, Atiah; Yudiana, Meigita; Wahidah, Miftahul; Nurmayeni (Buletin Ilmiah Pendidikan, 2023)
This research describes the implementation of the school literacy movement at SDN 88 Pekanbaru. The type of research chosen is a qualitative approach, the instruments used are interview guidelines and observation guidelines. The results showed that the implementation of the school literacy movement (GLS) at SDN 88 Pekanbaru had not been carried out optimally. Literacy is a language skill possessed by a person in communicating reading, spe aking, listening and writing, one of the most common supports for literacy is the library, schools can implement a library visit program. The library visit program is an organized activity that is applied to students regularly every week with different classes to carry out literacy activities. Qualitative research is research that is descriptive in nature and tends to use analysis. Process and meaning (subject perspective) are emphasized in qualitative research. The theoretical basis is used as a guide so that the research focus is in accordance with the facts in the field. In addition, this theoretical basis is also useful for providing an overview of the research setting and as material for discussing research results.